2012
DOI: 10.1007/s00395-012-0321-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced macrophage autophagy in atherosclerosis: for better or worse?

Abstract: Autophagy is a reparative, life-sustaining process by which cytoplasmic components are sequestered in double membrane vesicles and degraded upon fusion with lysosomal compartments. Mice with a macrophage-specific deletion of the essential autophagy gene Atg5 develop plaques with increased apoptosis and oxidative stress as well as enhanced plaque necrosis. This finding indicates that basal autophagy in macrophages is anti-apoptotic and present in atherosclerotic plaques to protect macrophages against various at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 83 publications
0
35
0
Order By: Relevance
“…Evidence showing that atherosclerosis progression is accompanied by increasing defects in macrophage autophagy provides further enthusiasm regarding the possibility that enhancement of macrophage autophagy may be an effective way to reduce or reverse atherosclerosis. However, currently known autophagy inducers, including mTOR inhibitors and toll-like receptor (TLR)7 ligands, are less than ideal therapeutics in the context of atherosclerosis, due to hyperlipidemic (24) and pro-inflammatory effects, respectively (25). Therefore, the search for new macrophage autophagy stimuli is urgent.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Evidence showing that atherosclerosis progression is accompanied by increasing defects in macrophage autophagy provides further enthusiasm regarding the possibility that enhancement of macrophage autophagy may be an effective way to reduce or reverse atherosclerosis. However, currently known autophagy inducers, including mTOR inhibitors and toll-like receptor (TLR)7 ligands, are less than ideal therapeutics in the context of atherosclerosis, due to hyperlipidemic (24) and pro-inflammatory effects, respectively (25). Therefore, the search for new macrophage autophagy stimuli is urgent.…”
Section: Mtt Assaymentioning
confidence: 99%
“…The morbidity and mortality rates of AS is increasing. Hyperlipidemia is an important cause of pathological changes in AS, and lipid metabolism disorders and abnormal lipoprotein composition are key factors in the pathogenesis of AS (Hyafil et al, 2012;Martinet et al, 2012;Zhao et al, 2012). Safflower yellow (SY), a natural yellow pigment extracted from safflower petals, is a chalcone compound.…”
Section: Introductionmentioning
confidence: 99%
“…The present study reported that, besides decreasing ox-LDL-induced cholesterol accumulation, simvastatin intensified ox-LDL-induced macrophage autophagy. However, it remains noteworthy that drugs may directly induce macrophage autophagy in atherosclerosis, and certain drug-induced macrophage autophagy promotes a stable plaque phenotype (22). The results of the present study showed that simvastatin may directly induce macrophage autophagy, albeit only marginally.…”
Section: Discussionmentioning
confidence: 40%
“…In mammalian cells there are two types of autophagy: mTOR-dependent and mTOR-independent autophagy (22). Wei et al (14) demonstrated that simvastatin induced autophagy through inhibition of Rac1-mTOR signaling in coronary arterial myocytes.…”
Section: Discussionmentioning
confidence: 99%